2003
DOI: 10.1088/0022-3727/36/8/310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing on wettability of quartz surfaces modified by Ar implantation

Abstract: Ion implantation is a powerful technique to modify the contact angles of surfaces. However, a change of the contact angle with the passage of time, called ageing, is observed on most surfaces. This paper aims to better understand the mechanism leading to the ageing of quartz surfaces implanted by argon ion. Coupons of quartz have been irradiated by 3 keV Ar ions to a fluence of 1.8×1016 Ar cm−2. Some implantations were performed under oxygen partial pressure (∼5×10−5 Torr). The samples have been characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Nevertheless, it was tested against independent measurements of contact angles at general conditions. Measurements of θ A and θ R were obtained from 14 sources in the open technical literature [5,8,[16][17][18][19][20][21][22][23][24][25][26][27], covering a wide variety of liquids and surfaces, including different liquid compositions and surface conditions. Data for ultra-hydrophobic surfaces were also included, although they fall outside the applicable range of the current model.…”
Section: Contact Angle Hysteresismentioning
confidence: 99%
“…Nevertheless, it was tested against independent measurements of contact angles at general conditions. Measurements of θ A and θ R were obtained from 14 sources in the open technical literature [5,8,[16][17][18][19][20][21][22][23][24][25][26][27], covering a wide variety of liquids and surfaces, including different liquid compositions and surface conditions. Data for ultra-hydrophobic surfaces were also included, although they fall outside the applicable range of the current model.…”
Section: Contact Angle Hysteresismentioning
confidence: 99%
“…Especially for run S5, the contact angle quickly rises from very low values and stabilizes at about 50°. This evolution could be due to the spreading of a hydrophobic carbonaceous contamination-layer on the silicon oxide film, as demonstrated by Ross et al [45]. In their case, the aging of quartz after ion implantation was studied.…”
Section: Agingmentioning
confidence: 91%
“…As PE is hydrophobic, this trend can explain the variations of the contact angle. The very low contact angle obtained for run S5 is then due to the complete coverage of the powders by a low contact angle silicon oxide (for instance, the contact angle of quartz is 38° [45]) and to the presence of silanol groups at the surface. So, depending on the operating conditions, the growth process can lead either to discontinuous coated zones or to a complete coverage of the powder.…”
Section: Influence Of the Oxygen Flow Ratementioning
confidence: 96%
“…Time (Weeks) Most work [25,26,31] focuses on the variation of contact angle over 28 days and does not consider any long term effects post-28 days. This could be of some significance as it can be seen through Figures 6 and 7 that the contact angle dramatically decreases for all samples after the 4 week hydrophobic recovery period.…”
Section: Wettability and Surface Chemistrymentioning
confidence: 99%
“…A number of various long term studies have been carried out investigating the effect of different parameters on the wettability of a material over a set amount of time [23][24][25][26]. In addition to long term studies it has also been observed that the differing atmospheric pressure and differing environments can have a major effect on the wettability of a material as seen by Li et al [27], Hansen et al [28] and Siemons et al [29].…”
Section: Introductionmentioning
confidence: 99%